1988
DOI: 10.1029/wr024i010p01569
|View full text |Cite
|
Sign up to set email alerts
|

An econometric study of industrial water demands in British Columbia, Canada

Abstract: Despite the importance of water use by the industrial sector, little economic research has been conducted to study the nature of industrial water demands,. This paper uses a relatively simple model of input demands to test whether industrial water use is sensitive to changes to input prices or the level of production. Demands for four aspects of industrial water use (intake, treatment prior to use, recirculation, and treatment prior to discharge) are estimated as a system of simultaneous equations. The data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 5 publications
4
28
2
1
Order By: Relevance
“…inelastic demand). This result is within the range of values previously obtained for service users (Williams and Suh 1986;Schneider and Whitlach 1991), and industrial users (Babin et al 1982;Williams and Suh 1986;Renzetti 1988;Reynaud 2003). This finding is not surprising when two issues are considered: firstly, service and industrial users think they are paying less than the actual price, as shown by the estimated value of the price perception parameter ( k = 6.004); secondly, service and industrial users are subject to the same price levels as residential users.…”
Section: Resultssupporting
confidence: 86%
“…inelastic demand). This result is within the range of values previously obtained for service users (Williams and Suh 1986;Schneider and Whitlach 1991), and industrial users (Babin et al 1982;Williams and Suh 1986;Renzetti 1988;Reynaud 2003). This finding is not surprising when two issues are considered: firstly, service and industrial users think they are paying less than the actual price, as shown by the estimated value of the price perception parameter ( k = 6.004); secondly, service and industrial users are subject to the same price levels as residential users.…”
Section: Resultssupporting
confidence: 86%
“…With the cost function approach, it is assumed that firms choose water and the others inputs in order to minimize the production cost for a given level of output. Some specific applications of the cost function approach for valuing water include Renzetti (1988) and Dupont and Renzetti (2001) in Canada, Reynaud (2003) in France, and Féres and Reynaud (2005) in Brazil. With the production function approach (primal approach), the marginal value of water is obtained from the estimated production function, see Wang and Lall (2002) for a specific application for valuing water used by industrial plants in China.…”
Section: Valuationmentioning
confidence: 99%
“…Studies on the demand for water can be divided into three main groups: (i) residential demand for water (Mu et al 1990;Madanat and Humplick, 1993); (ii) industrial demand for water, (Renzetti, 1988); and (iii) agricultural demand for water (Ogg and Gollehon, 1989).…”
Section: The Demand For Watermentioning
confidence: 99%